The newspapers handbook - Keeble, Richard (Media skills)
"This new edition of The Newspapers Handbook presents an enlightening examination of an ever-evolving industry, engaging with key contemporary issues, including reporting in the digital age and ethical and legislative issues following the hacking scandal to display a comprehensive anatomy of the modern newsroom. Richard Lance Keeble and Ian Reeves offer readers expert practical advice, drawing on a wide range of examples from print and digital news sources to illustrate best practice and the political, technological and financial realities of newspaper journalism today. Other key areas explored include: the language of newsbasic reportingthe art of interviewingfeature writing the role of social media in reporting investigative reporting court reportingreporting on national and local government guidance on training and careers for those entering the industry"--